1993
DOI: 10.1111/j.1365-2672.1993.tb05194.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxin production by Fusarium culmorum IMI 309344 and F. graminearum NRRL 5883 on grain substrates

Abstract: The production of deoxynivalenol, acetyl deoxynivalenol and zearalenone by Fusarium culmorum and F. graminearum on autoclave‐sterilized grain (maize, rice, wheat and barley) was investigated. Fusarium culmorum produced significantly greater levels of toxins than F. graminearum. The four substrates examined differed in their ability to support toxin production. Toxin production on maize and rice was significantly greater than toxin production on barley or wheat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The occurrence of different trichothecene-producing isolates of G. zeae reported here and in previous studies (2,7,18,22,34) may be due to the relatively wide range of environmental conditions under which the host crops are grown. In particular, temperature and precipitation (11,14) and substrate composition (31) were reported previously to be major factors influencing trichothecene production by G. zeae. We hypothesize that the uniqueness of the environment may play an important role in the trichothecene diversity in G. zeae populations in the region.…”
Section: Vol 74 2008 Mycotoxin Production By Gibberella Zeae 6517mentioning
confidence: 94%
“…The occurrence of different trichothecene-producing isolates of G. zeae reported here and in previous studies (2,7,18,22,34) may be due to the relatively wide range of environmental conditions under which the host crops are grown. In particular, temperature and precipitation (11,14) and substrate composition (31) were reported previously to be major factors influencing trichothecene production by G. zeae. We hypothesize that the uniqueness of the environment may play an important role in the trichothecene diversity in G. zeae populations in the region.…”
Section: Vol 74 2008 Mycotoxin Production By Gibberella Zeae 6517mentioning
confidence: 94%
“…Trichothecene biosynthesis may be regulated by environmental conditions such as temperature (20,56), water activity (12,20), substrate composition (13,44), etc. Nevertheless, it is also well established that, within the same species and under optimal conditions of growth, some strains produce large amounts of trichothecenes, whereas other strains produce small or undetectable amounts of trichothecenes (15,19,24,30,35,36,57).…”
Section: Discussionmentioning
confidence: 99%
“…O'Neill et al (1993) reported that 14 days or more was required for DON to be detected after grain was inoculated with F. graminearum. All fungi normally found on grains produce ergo- sterol.…”
Section: Relationship Of Don and Ergosterol To Scabmentioning
confidence: 99%
“…Thus, the presence of ergosterol may either indicate the presence of other fungi, or that ergosterol was present before DON was produced. O'Neill et al (1993) reported that 14 days or more was required for DON to be detected after grain was inoculated with F. graminearum.…”
Section: Relationship Of Don and Ergosterol To Scabmentioning
confidence: 99%